1998
DOI: 10.1111/j.2044-8260.1998.tb01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers, daughters and dieting: Investigating the transmission of weight control

Abstract: The parallel with the findings of Pike & Rodin supports the role that mothers may play in the transmission of cultural values regarding weight, shape and appearance. Importantly, it also places early dieting within a wider context of dissatisfaction with family functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
2
10

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 17 publications
4
76
2
10
Order By: Relevance
“…Nutrition-related habits of Greek adolescents M Yannakoulia et al biological (BMI status), social (family influences, maternal attitudes and behaviors, and peer pressures), cultural factors (media influences), and personal processes (self-esteem and confidence) (Hill & Franklin, 1998;Taylor et al, 1998;Huon & Walton, 2000). For girls in particular, puberty is a critical and challenging time, being at risk of low self-esteem and body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition-related habits of Greek adolescents M Yannakoulia et al biological (BMI status), social (family influences, maternal attitudes and behaviors, and peer pressures), cultural factors (media influences), and personal processes (self-esteem and confidence) (Hill & Franklin, 1998;Taylor et al, 1998;Huon & Walton, 2000). For girls in particular, puberty is a critical and challenging time, being at risk of low self-esteem and body dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Within the family, the mother is a primary role model and seems to be a powerful influence on daughters. Some authors found that the mothers of girls with disordered eating patterns were more critical of their daughters' appearance than the mothers of healthy girls [13], and that children's attempts to lose weight were related to parental comments about their weight and to children's own complaints about their own weight [25]. Mothers of children with ED had higher bulimic factor scores in the Eating Attitudes Test-26, more binge-eating episodes, and more ED symptoms than those in a control group [9].…”
Section: Introductionmentioning
confidence: 99%
“…Blissett, Meyer, Farrow, Bryant-Waugh & Nicholls (2005) suggested that different expectations for social norms for male and female children, and maternal anxiety about achieving these ideals, may help to explain the different relationships between mental health and reported problems for mothers of girls and boys. The parent"s anxiety about the child"s achievement of specific gender-linked goals, such as the achievement of slimness by girls and greater height and weight by boys (Hill & Franklin, 1998;Pierce & Wardle, 1993;Tiggemann, & Lowes, 2002), may be associated with carrying out gender-specific parenting practices designed to facilitate the achievement of these goals, such as pressurizing or controlling food intake, despite their ultimately negative outcome (Costanzo & Woody, 1985;Fisher & Birch, 1999). Indeed it has been previously shown that maternal eating psychopathology is related to controlling feeding practices in mothers of girls but not boys (Blissett, Meyer & Haycraft, in press;Tiggemann & Lowes, 2002;Jacobi, Agras & Hammer, 2001).…”
Section: Maternal Mental Health and Child Feeding Problems In A Non-cmentioning
confidence: 99%